2015
DOI: 10.3141/2526-10
|View full text |Cite
|
Sign up to set email alerts
|

GPS and Acceleration Data in Multimode Trip Data Recognition Based on Wavelet Transform Modulus Maximum Algorithm

Abstract: The GPS-based travel survey is an emerging data collection method in transportation planning. The survey's application in trip mode detection has been explored in many studies. Most research on trip mode detection methods based on GPS data has been developed and tested with data collected from European and American countries. The methods cannot be easily adapted to Asian countries such as China, India, and Japan, which have much higher population densities, more complex road networks, and highly mixed travel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…Em [15] foi utilizada a técnica de redes neurais para inferir o modo de transporte em cada segmento da viagem. Como resultado, foi detectado um nível de precisão na inferência de mais de 86%.…”
Section: Trabalhos Relacionadosunclassified
“…Em [15] foi utilizada a técnica de redes neurais para inferir o modo de transporte em cada segmento da viagem. Como resultado, foi detectado um nível de precisão na inferência de mais de 86%.…”
Section: Trabalhos Relacionadosunclassified
“…The reference lists of excluded reviews were reviewed and potential papers were gathered. Finally, 12 published papers matching all the criteria were included in this review [1,31,[38][39][40][41][42][43][44][45][46][47], as shown in Table 2. In particular, we selected [39] because the segment identification method of this study is a significant data preprocessing technique for travel mode detection.…”
Section: Systematic Review Processmentioning
confidence: 99%
“…However, the data preprocessing procedure was not mentioned in these papers [41,45]. The data preprocessing methods were simply referred to in papers [1,31,38,47].…”
Section: Data Preprocessing Proceduresmentioning
confidence: 99%
See 2 more Smart Citations